2011 Triennial Surveillance Review : External Commentary. (Policy Papers; Policy Paper, 2011)
Commentary prepared by Martin Wolf, Associate Editor and Chief Economics Commentator, Financial Times, London: "With countries naturally reluctant to cede any control over their own monetary and fiscal policies, it is likely that the IMF will have as instruments only the powers of analysis, persuasion, and, in Keynes" own favourite words, "ruthless truth-telling". That phrase does not conjure up many memories of any of the many international meetings I have attended. But unless the IMF has the self-confidence to play that role, its deliberations and statements will carry little weight. The Fund requires an independent, respected and clear voice." Mervyn King, 2006.